“Can I use the toilet?”: Watching Steven Moffat’s Doctor Who (2010- 2017) as Posthuman Television - Hay, Jonathan (Journal of Posthumanism, 2022)
Interpreting the modern television series Doctor Who as an extended metaphor of everyday posthuman life, this article explicates the postphenomenological qualities of the six series released during Steven Moffat’s tenure as showrunner. By explicating precisely how the show’s televisual format amplifies and intersects with its overtly technology-centred narrative content, I develop a posthumanistic conception of Doctor Who’s intra-active rhetorical strategies. This era of the show illustrates the vital role played by the cultural imaginaries of our contemporary lifeworlds upon the realisation of the posthuman future, by vicariously implicating viewers in its mundane discourse. Additionally, its narrative penchant for frequent timeline resets is symptomatic of the intra-active engagements formed between viewers and the technological apparatus of the series itself. By closely analysing a representative sample of episodes, I demonstrate that by watching Doctor Who, viewers are interpellated to recognise their agential capacity to inform our species’ posthuman potential.